In situ synthesis of a high-performance bismuth oxide based composite cathode for low temperature solid oxide fuel cells - Fang, Wei (2021)
Here, we report the design and fabrication of a cost-effective and high-performance composite (Bi0.75Y0.25)0.93Ce0.07O1.5d–La0.8Sr0.2MnO3 cathode by an in situ synthesis strategy with single-step phase formation and microstructure assembly, which shows lower cathode polarization resistance and better oxygen reduction reaction activity than the conventional LSM-based cathodes for low temperature solid oxide fuel cells.